Nurturing and management of talent in motorsport - Syarizal Abdul Rahim; Mohd Firdaus Mohd Nasir; Razli Che Razak (2015)
This paper examined the dualist nature of a student sportsperson while performing in two wheel motorbike racing. The study aimed to identify the sociological implications of the key aspects that affecting the optimal career development in racing. The method used for this study is a qualitative case study on the current race participants in Malaysia Super Series and Cub Prix. Interviews were held as part of a purposive sample. Data was collected over a period of six months with eight riders which consist of four student racer, 3 after school racer and two racing club owners. The study designed for allowing an input, throughput and output analysis. In determining the rationale of the input and throughput phases, qualitative data were integrated for the identification of major themes and trends. All racers which currently still studying at a secondary level, demonstrated a relatively extensive and powerful socialization process. Parents, coach and peers are the main social agents during the primary and secondary school years which were discovered during this study. The attention swift to club owners (including the coach) and fellow racer during the post study at secondary level. There are an increasing need for an academic support at secondary level with critical issues around time, career and management of lifestyle. During the final socialization and specialization, most students recent faced various career challenges without receiving adequate and proper guidance towards breaking the socialization and becoming a professional racer.